Sufi dan Perempuan: Studi Gerakan Perempuan Hajjah Naziha Adil al-Haqqani - Siswoyo Aris Munandar (UIN Sunan Kalijaga Yogyakarta, 2022)
The lack of texts about the contribution of female Sufis, but there are several female Sufis who spread the doctrine and practice of Sufism, namely Rabi'ah and Aishah al-Ba'uniyyah are two big names and female Sufis who prove that women have equal opportunities in attainment of spiritual knowledge. Therefore, writers are interested in female Sufis, especially in Western countries, where so far many writers have focused on female Sufis in the eastern world, therefore it is very interesting to discuss about female Sufis in the West, namely Hajjah Naziha, a female Sufi who has a movement. philanthropy at the international level. This study uses a qualitative descriptive approach and reviews the literature such as books, journals, articles, and various sources that are relevant to the theme of the discussion in this paper. The results of the study explained that female Sufis namely Hajjah Amina Adil and Hajjah Naziha Adil with their organization called HNCO (Hajjah Naziha Charitable Organization) were involved in philanthropy. The movement has spread its wings to several countries and continues to help the community, especially those who limit the spread of COVID-19.